2016
DOI: 10.1007/s11999-016-4976-z
|View full text |Cite
|
Sign up to set email alerts
|

The Biologic Response to Polyetheretherketone (PEEK) Wear Particles in Total Joint Replacement: A Systematic Review

Abstract: BackgroundPolyetheretherketone (PEEK) and its composites are polymers resistant to fatigue strain, radiologically transparent, and have mechanical properties suitable for a range of orthopaedic applications. In bulk form, PEEK composites are generally accepted as biocompatible. In particulate form, however, the biologic response relevant to joint replacement devices remains unclear. The biologic response to wear particles affects the longevity of total joint arthroplasties. Particles in the phagocytozable size… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
53
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 76 publications
(59 citation statements)
references
References 41 publications
1
53
0
Order By: Relevance
“…In this study, the mean particle size of PEEK and HXLPE was found to be approximately 0.1-10 mm, which is generally considered the most biologically reactive size range. 1,15,16 In addition, the particle sizes and size distributions of the two particles types were similar, as measured by LALLS and SEM analyses. Lymphocyte activation requires a major histocompatibility complex (MHC)-associated antigen-specic signal, as well as a simultaneous "costimulatory" signal by antigen presenting cells (APCs).…”
Section: 614supporting
confidence: 63%
See 1 more Smart Citation
“…In this study, the mean particle size of PEEK and HXLPE was found to be approximately 0.1-10 mm, which is generally considered the most biologically reactive size range. 1,15,16 In addition, the particle sizes and size distributions of the two particles types were similar, as measured by LALLS and SEM analyses. Lymphocyte activation requires a major histocompatibility complex (MHC)-associated antigen-specic signal, as well as a simultaneous "costimulatory" signal by antigen presenting cells (APCs).…”
Section: 614supporting
confidence: 63%
“…[7][8][9] Particles in the phagocytosable size range (0.1-10 mm) are considered the most biologically reactive, particularly particles with a mean size <1 mm. 1,10,11 Wear debris have been shown to elicit immune responses with increased inammatory marker secretion from macrophages.…”
mentioning
confidence: 99%
“…However, PEEK relies on large graft windows to allow fusion as its smooth surface, hydrophobic properties and lack of porosity do not facilitate bony ongrowth, ingrowth and through-growth [21]. Its lack of incorporation into bone leads to shedding of submicron particles which drive osteolysis manifesting in inflammation [22,23].…”
Section: Discussionmentioning
confidence: 99%
“…This suggests that the damaged surface may also exhibit some cytotoxic features. These and the remaining tests on PEEK composites, were carried out mainly for carbon fillings, which directly creates the need to conduct similar research over glass-reinforced PEEK (PEEK GRF) [26][27][28][29]. PEEK GRF with 30% of the reinforcement (PEEK GRF30) finds its use in i.a.…”
Section: Introductionmentioning
confidence: 99%